An archaeology of the immaterial - Buchli, Victor., author.
1 online resource (x, 189 pages)
Keywords: "An Archaeology of the Immaterial examines a highly significant but poorly understood aspect of material culture studies: the active rejection of the material world. This is evident in a number of cultural projects, including anti-consumerism and asceticism, as well as other attempts to transcend material circumstances. Exploring the cultural work which can be done when the material is rejected, and the social effects of these 'dematerialisations', this book looks at the way people 'disengage' from the world as a specific kind of physical engagement which has profound implications for our understanding of personhood and materiality. Using case studies which range widely in time over Western societies and the technologies of materialising the immaterial, from icons to the scanning tunnelling microscope, Buchli addresses the significance of immateriality for our own economics, cultural perceptions, and emerging forms of social inclusion and exclusion. An Archaeology of the Immaterial is thus an important and innovative contribution to material cultural studies, demonstrating that the making of the immaterial as well as the material are both profoundly powerful operations which work to exert social control and delineate the borders of the imaginable and the enfranchised"--Provided by publisher.